2021
DOI: 10.1002/pro6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Radiotherapy of Esophageal Carcinoma (2020 Edition)

Abstract: Esophageal carcinoma is a high-incidence malignant tumor in China, ranking sixth and fourth highest in morbidity and mortality, respectively. Radiotherapy plays an important role in the comprehensive treatment of esophageal carcinoma. Standardized diagnosis and treatment based on the suggestions of a multidisciplinary team (MDT) form its foundation. For operable esophageal carcinoma, surgery after neoadjuvant chemoradiotherapy is the standard treatment; contrarily, for inoperable esophageal carcinoma, radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The recommended dose for palliation is itself a bit variable, with a range of 20 to 40 Gy across the guidelines. 3 , 4 , 5 , 8 , 13 , 14 , 15 , 16 In the current study, 64.8% of the patients who received radiation received less than 45 Gy, 29% received between 45 and 59.9 Gy, and 2.2% received considerably more radiation (60–80 Gy).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The recommended dose for palliation is itself a bit variable, with a range of 20 to 40 Gy across the guidelines. 3 , 4 , 5 , 8 , 13 , 14 , 15 , 16 In the current study, 64.8% of the patients who received radiation received less than 45 Gy, 29% received between 45 and 59.9 Gy, and 2.2% received considerably more radiation (60–80 Gy).…”
Section: Discussionmentioning
confidence: 45%
“…These categories were chosen to represent ranges for palliative and definitive dosing of external beam radiation therapy. 3 , 4 , 5 , 13 , 14 , 15 , 16 In a manner consistent with previous studies, 17 , 18 age was included as a categorical variable (18–34, 35–49, 50–64, 65–79, ≥80 y). Survival models with age as a continuous variable were created as sensitivity analyses, yielding similar results (data available on request).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal stenting can be done to relieve dysphagia and improve quality of life. Common sites of distant metastases include lungs, pleura, liver, brain, and bone, with greater tumor size at diagnosis being a poor prognostic factor [ 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant fluorouracil-based chemotherapy and chemoradiotherapy are recommended in lymph node-positive patients, keeping node-negative patients on regular monitoring. Recent trials have suggested the use of immunotherapy like pembrolizumab, camrelizumab, and nivolumab in concurrence with chemotherapy or second-line agents [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%